2003
DOI: 10.1016/j.rmed.2003.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac or pulmonary dyspnea in patients admitted to the emergency department

Abstract: A simple and quick way of discrimination between cardiac and pulmonary causes of dyspnea is essential in patients admitted to the emergency department. We aimed to assess the utility of easily applicable diagnostic tools in the differential diagnosis of cardiac and pulmonary causes of dyspnea in patients presenting with shortness of breath. Clinical and radiologic evaluation, peak expiratory flow (PEF), PaO2, PaCO2 measurements were performed in 94 patients admitted to the emergency room with dyspnea. All the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 11 publications
0
8
1
1
Order By: Relevance
“…23 Moreover, in order to distinguish between cardiac and pulmonary dyspnoea, measurements of PEF, P aO2, PaCO2 and indices of these variables are necessary tools in the ER. 24 The percentage of OPD patients who had arterial blood gas concentrations measured in our study (84%) is considerably higher than the recording rate of 64% in 70,000 patients admitted to hospital with acute exacerbations of COPD in the USA. 25 Several papers 26,27 indicate that physicians often fail to use spirometry for routine monitoring of asthma and COPD.…”
Section: Discussioncontrasting
confidence: 63%
“…23 Moreover, in order to distinguish between cardiac and pulmonary dyspnoea, measurements of PEF, P aO2, PaCO2 and indices of these variables are necessary tools in the ER. 24 The percentage of OPD patients who had arterial blood gas concentrations measured in our study (84%) is considerably higher than the recording rate of 64% in 70,000 patients admitted to hospital with acute exacerbations of COPD in the USA. 25 Several papers 26,27 indicate that physicians often fail to use spirometry for routine monitoring of asthma and COPD.…”
Section: Discussioncontrasting
confidence: 63%
“…Symptoms of dyspnea result from complex interactions between signals from the central nervous system and receptors in the upper airway, lungs, and chest wall (Carrieri-Kohlman, Lindsey, & West, 2003;Mahler & O'Donnell, 2005). Most conditions that cause dyspnea probably do so by more than one mechanism, and different conditions may share common mechanisms (American Thoracic Society, 1999;Malas et al, 2003). Dyspnea is thought be related to a variety of factors such as the clinical characteristics of the condition and, possibly, to psychosocial factors specific to the individual patient.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies have evaluated the use of PEFR for the diagnosis of patients with AHF (11)(12)(13). All found that patients with AHF could be readily distinguished from those with chronic lung disease by PEFR; however, its value for the diagnosis of heart failure (HF) is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Three measurements were completed at each time point, with the highest PEFR recorded in l/min (11)(12)(13). Other data captured simultaneously included respiratory rate in breaths/min, oxygen saturation (%), and liters of oxygen delivered (in l/min).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation